The Impact of Green Economy to enhance Sustainable Development Goals” - HELMI , Driss; NADIRI , Lina (Revue Internationale des Sciences de Gestion, 2024)
During the last decade, the world suffered from environmental, climate and health changes which have clearly impacted the development of different Sustainable Development goals (SDGs).For that, the growing appetite for Green Economy is clearly seen aiming at environmentally friendly projects, especially in Morocco. In this study, we will use a comparative method that examines relationships, influence and associations between countries in Africa. After that, we will be using a conservative (Maximin) model by stating which country has the most contribution on Green Finance. Moreover, this study will investigate the relationship; association and contribution of Green Economy in the enhancement of Sustainable Development Performance in Morocco in comparison with others African geographically, culturally and linguistically close but economically and financially diversified countries that hold different gross domestic products citing South Africa, Egypt, Kenya and Rwanda. Thus, it will meet the objective of measuring the contribution of some countries to enhance their Sustainable Development Performance. Our findings will prove that this study is an added value to the research world by making greater theoretical contributions, filling gaps and improving life satisfaction in Morocco, Africa and the World.